New diamide-diamine ligands and their zirconium and hafnium dichloride and bis(dimethylamide) complexes. - Skinner, M; Li, Y; Mountford, P (2002)
The multigram syntheses of the protio ligands (2-NC(5)H(4))CH(2)N(CH(2)CH(2)NHSiMe(2)R)(2) (R = Me, H(2)N(2)NN' 3; R = (t)Bu, H(2)N(2)NN() 4) are described via reactions of the previously reported (2-NC(5)H(4))CH(2)N(CH(2)CH(2)NH(2))(2) (1). A new synthesis of 1 is reported starting from 2-aminomethylpyridine and N-tosylaziridine, proceeding via (2-NC(5)H(4))CH(2)N(CH(2)CH(2)NHTs)(2) (2). Reaction of H(2)N(2)NN' or H(2)N(2)NN* with (n)BuLi gives good yields of the dilithiated derivatives Li(2)N(2)NN' and Li(2)N(2)NN*. Reaction of H(2)N(2)NN' or H(2)N(2)NN* with [MCl(2)(CH(2)SiMe(3))(2)(Et(2)O)(2)] gives the cis-dichloride complexes [MCl(2)(L)] (L = N(2)NN', M = Zr 7 or Hf 8; L = N(2)NN(), M = Zr 9). The corresponding reactions of H(2)N(2)NN' or H(2)N(2)NN* with [Zr(NMe(2))(4)] afford the bis(dimethylamide) derivatives [Zr(NMe(2))(2)(L)] (L = N(2)NN' 10 or N(2)NN* 11). All of these protonolysis reactions proceed smoothly and in good yields. Attempts to prepare the titanium complexes [Ti(X)(2)(N(2)NN')] (X = Cl or NMe(2)) were unsuccessful. The X-ray crystal structures of (2-NC(5)H(4))CH(2)N(CH(2)CH(2)NHTs)(2).EtOH, [ZrCl(2)(N(2)NN')].0.5C(6)H(6), [Zr(NMe(2))(2)(N(2)NN')], and [Zr(NMe(2))(2)(N(2)NN*)] are reported.